The Influence of Transformational Leadership, Work Environment and Compensation on Employee Job Satisfaction at Bento Kopi Yogyakarta - Hakam Fauzi; Prayekti Prayekti; Landri Landri (Jurnal Ilmu Manajemen Profitability, 2023)
This study aims to determine whether there is a partial and simultaneous influence of transformational leadership, work environment, compensation, on employee job satisfaction at Bento Kopi Yogyakarta. The nature of this research iscausal associative research through quantitative approach research with a research population of 120 people, which are all employees of Bento Kopi Yogyakarta. The sampling technique of this study used probability sampling (simple random sampling) with the Slovin formula on the research population, namely Bento Kopi Yogyakrta employees, so that a sample of 86 employees was obtained as research respondents. Data collection techniques using questionnaires distributed to 92 respondents. The data analysis technique uses validity test, reliability test, descriptive statistics, classical assumption test, multiple linear regression test, hypothesis test and coefficient of determination. The results of this study indicate that transformational leadership has a positive and significant effect on employee job satisfaction. The work environment has no partial effect on employee job satisfaction. Compensation has a positive effect on employee job satisfaction. Transformational Leadership, Work Environment and Compensation have a simultaneous and significant positive effect on Job Satisfaction on employees at Bento Kopi Yogyakarta